UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA MATERI PECAHAN SENILAI MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE TGT BERBANTUAN MEDIA “DIGITAL SMART BOOK” PADA SISWA KELAS IV DI SDN 02 TEGUHAN - Dhios Nomeda Bimantara; Fachrur Rossy Handoko; Melik Budiarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This classroom action research aimed to improve the mathematics learning outcomes of fourth-grade students at SDN 02 Teguhan, focusing on the topic of equivalent fractions. The problem was triggered by the low initial performance of students and the use of conventional learning methods. To address this, the study implemented the Cooperative Learning model of the Teams-Games-Tournament (TGT) type supported by the Digital Smart Book as an interactive media tool. The research was conducted in two cycles, each consisting of planning, action, observation, and reflection. Data were collected through pre-tests, post-tests, observations, documentation, and interviews. Results showed a significant increase in students’ cognitive performance, with the average score improving from 50.3 in the pre-test to 89.3 in the second cycle. The percentage of students achieving the minimum mastery criteria (KKM) rose from 0% in the pre-test to 100% by the second cycle. The integration of the TGT model and Digital Smart Book media effectively enhanced student engagement, collaboration, and understanding of abstract mathematical concepts. Therefore, this approach is considered a promising and innovative alternative for teaching mathematics at the elementary level